Analisis Dan Mitigasi Resiko Rantai Pasok Dengan Metode AHP Dan FMEA - Wiwik Handayani; Muhammad Adam Yusuf (REVITALISASI : Jurnal Ilmu Manajemen, 2022)
During the Covid-19 pandemic, the economy in Indonesia experienced a decline, especially MSMEs. It is important for MSMEs to switch strategies in dealing with this pandemic, one of which is by using an online system in the sales process, as was done by MSMEs "SwiitieandSalty". This move to an online system has created a new risk for MSMEs, namely supply chain problems. The purpose of this study is to analyze the risks experienced by using the FMEA and AHP methods. The results of this study are that there are two types of risks that need to be prioritized, namely the risk of late delivery at the Situbondo agent with an RPN value of 8.15 and the risk of product damage to the Jakarta agent with an RPN value of 9.24.